2010
DOI: 10.1007/s00248-010-9712-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oral Microbiota in Children with Dental Caries by PCR-DGGE and Barcoded Pyrosequencing

Abstract: Oral microbiota plays a vital role in maintaining the homeostasis of oral cavity. Dental caries are among the most common oral diseases in children and pathogenic bacteria contribute to the development of the disease. However, the overall structure of bacterial communities in the oral cavity from children with dental caries has not been explored deeply heretofore. We used high-throughput barcoded pyrosequencing and PCR-denaturing gradient gel electrophoresis (DGGE) to examine bacterial diversity of oral microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
177
4
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(231 citation statements)
references
References 68 publications
47
177
4
3
Order By: Relevance
“…These findings imply that the onset of dental caries has an association with a lower diversity of oral streptococci, which is consistent with a cross-section study of preschool children in the various stages of dental caries (Jiang et al, 2011). According to these findings and the previous studies, we infer that the decline in streptococcal diversity in S-ECC plaques is possible because of shifts in the balance of the resident plaque microbiota (Jiang et al, 2011;Li et al, 2007;Ling et al, 2010). Bacterial species present in the dental biofilm communities have cooperative or competitive interactions with other members (Guo et al, 2014).…”
Section: Oral Streptococci Succession Associated With S-eccsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings imply that the onset of dental caries has an association with a lower diversity of oral streptococci, which is consistent with a cross-section study of preschool children in the various stages of dental caries (Jiang et al, 2011). According to these findings and the previous studies, we infer that the decline in streptococcal diversity in S-ECC plaques is possible because of shifts in the balance of the resident plaque microbiota (Jiang et al, 2011;Li et al, 2007;Ling et al, 2010). Bacterial species present in the dental biofilm communities have cooperative or competitive interactions with other members (Guo et al, 2014).…”
Section: Oral Streptococci Succession Associated With S-eccsupporting
confidence: 78%
“…Such data could reflect the general microbial composition in dental plaque of the exposed tooth surface, compared with sitespecific plaque sampling, for which data reflect only the situation of specific colonized sites (Tanzer et al, 2001). Previously, we and others demonstrated that PCR-DGGE is a valuable tool for intuitively observing the dynamics of microbial communities composing the dental plaque of children (Jiang et al, 2011;Li et al, 2007;Ling et al, 2010;Tao et al, 2013). In the present study, we sequenced the rnpB gene combined with DGGE to evaluate the diversity and dynamics of oral streptococci associated with S-ECC.…”
Section: Oral Streptococci Succession Associated With S-eccmentioning
confidence: 99%
See 1 more Smart Citation
“…polymorphum , Veillonella spp., Actinomyces, K. oralis , C. matruchotii , C. gracilis , C. curvus , S. gordonii , S. mutans , S. mitis bv. 2, S. cristatus , S. anginosus , cloning, 16S rRNA gene sequencing 84M 73 L. wadei , Leptotrichia spp.Immunocompetent, pneumonia, hypoxemia, sore throat, fever, dyspnea, cough, leukocytosis, RNote: 1st case of pneumoniaBALF, mouth-gargled water Staphylococcus spp., Acidaminococcus spp., Veillonella spp., V. parvula , V. atypica , V. dispar , Lactobacillus spp., Enterococcus spp., E. faecalis , E. casseliflavus , P. nanceiensis , culture, cloning, 16S rRNA gene sequencing[24]85M/F 3–6 Leptotrichia Caries-free male, male with caries, caries-free females, female with cariesSaliva, plaque Capnocytophaga , Peptostreptococcus, Corynebacterium , Rothia, Veillonella , Prevotella, Granulicatella , Streptococcus, Actinomyces , Thiomonas, Kingella , Campylobacter, Fusobacterium , Erysipelothrix, Atopobium , Oribacterium, Haemophilus , Neisseria , DGGE, HTS[25]86M/F 3–5 Leptotrichia spp.Moderate cariesPlaque Capnocytophaga , Corynebacterium, Campylobacter , Haemophilus, mitis group streptococci, mutans group streptococci, Neisseria, Burkholderia , Actinomyces, Prevotella , DGGE, cloning, 16S rRNA gene sequencing[26]M/F 3–5 Leptotrichia spp.Caries-susceptiblePlaque Capnocytophaga, Corynebacterium, Actinomyces , Burkholderia, mutans group streptococci, Neisseria, Haemophilus , Prevotella , DGGE, cloning, 16S rRNA gene sequencing M/F 3–5 Leptotrichia spp.Caries-freePlaque Mitis group streptococci, mutans group streptococci, Neisseria, Prevotella , Campylobacter, Burkholderia , Capnocytophaga, Corynebacterium , Actinomyces, Haemophilus , DGGE, cloning, 16S rRNA gene sequencing 89M/F 25–39 Leptotrichia spp.Unhealthy, gingivitisPlaque, saliva S. sanguinis , Veillonella, Prevotella , Neisseria, Fusobacterium , Rothia , TM7, H. parainfluenzae , Granulicatella, L. mirabilis , Selenomonas, Actinomyces , HTS, PCA[27]F 21–23 ± 18 Leptotrichia spp.…”
Section: Figurementioning
confidence: 99%
“…They were also recovered from oral plaque of guinea pigs [21] and feces of piglets [54], dental plaque from healthy individuals, plaque and saliva from patients with various types of caries, gingivitis, chronic periodontitis, and peri-implantitis [23,2527,34,35,37,38,44,45,47,49,52,59,60,62,6669,91,94], decayed tooth surfaces and discordant caries from intact enamel surfaces [53]. Leptotrichia species were also isolated from bronchoalveolar lavage fluid, and patients with leukocytosis, hypoxemia, and dyspnea [24].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%